Preparation method of biomass charcoal / magnesium composite negative electrode plate with high ionic conductivity

By chemically activating the biomass carbon and preparing it with magnesium in a pressure impregnation process, the problem of insufficient ion conductivity of the magnesium metal negative electrode is solved, the electrochemical performance is improved, and the sustainable utilization of biomass materials is achieved, and the The demand for magnesium ion protection interface has achieved efficient and low-cost electrochemical electrode sheet preparation.

CN119153633APending Publication Date: 2024-12-17HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411292097.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing magnesium metal negative electrodes are hindered by the ion passivation interface layer in conventional electrolytes, resulting in insufficient magnesium ion conductivity, affecting electrochemical performance, and lacking a simple and low-cost process to improve the ionic conductivity of biomass carbon. To meet the needs of magnesium ion protection interface.

Method used

By chemically activating the biomass carbon and hydrogen peroxide, modified biomass carbon with a large number of defects and large specific surface area is generated, and the negative electrode sheet of biomass carbon/magnesium composite material is prepared by a pressure impregnation process under a protective atmosphere. Improve the contact sites and transport paths of magnesium ions and optimize ion conductivity.

Benefits of technology

It significantly improves the chemical reaction rate and electrochemical performance of magnesium metal negative electrodes, realizes the sustainable conversion of biomass materials into functional materials, reduces the cost and environmental protection of electrochemical electrode sheets, and meets the needs of industrial production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153633A_ABST
    Figure CN119153633A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a biomass charcoal / magnesium composite negative electrode plate with high ionic conductivity, and relates to a preparation method of a novel biomass charcoal / magnesium composite negative electrode plate. The problem that the ionic conductivity of biomass charcoal serving as an artificial protection interface on the magnesium metal surface is not high is solved. According to the method for improving the ionic conductivity of the biomass charcoal / magnesium composite material, the biomass charcoal is subjected to etching treatment by utilizing hydrogen peroxide, so that the biomass charcoal generates a large number of defects, and the modified biomass charcoal / magnesium composite material is prepared by utilizing a self-exhaust pressure infiltration technology. The modified biomass charcoal serving as the artificial SEI on the surface of the magnesium metal negative electrode enables overpotential of a magnesium metal negative electrode plate to be obviously reduced in a circulation process in a conventional electrolyte, and reaction kinetics is effectively improved. The raw materials are low in cost, green, environment-friendly and renewable, the electrochemical pole piece is integrally prepared, simple and effective, the performance of an artificial protection interface can be effectively improved through simple activation treatment, and industrial production and application are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a novel biomass carbon / magnesium composite material negative electrode sheet. Background Art

[0002] Magnesium metal is a promising candidate for super lithium-ion battery anodes because the volumetric capacity of magnesium anodes is 3833 mAh / cm -3 , which is nearly the same as lithium metal (2046mAh cm -3 ); the magnesium negative electrode also has a low reduction potential (-2.37Vvs standard hydrogen electrode); in addition, magnesium metal resources are abundant, high safety performance, high energy density, low price and environmental protection are attracting more and more attention. In large-scale energy storage systems with low battery volume requirements, magnesium-ion batteries are expected to become the ideal choice for the next generation of battery systems.

[0003] In conventional electrolytes, the ion-passivating interfacial layer produced by the reduction of chemically unstable solvated species can hinder the Mg 0 / Mg 2+ reaction. A large number of studies have confirmed that biochar has a certain metal ion conductivity, and good ion conductivity in magnesium metal batteries is a prerequisite for biochar to become an artificial SEI (solid electrolyte interface) on the surface of the magnesium metal negative electrode. Therefore, further improving the ionic conductivity by modifying the biochar helps to improve the reaction kinetics of the magnesium metal negative electrode during the cycle. Therefore, by preparing a modified biochar / magnesium composite material by combining the modified biochar and magnesium metal, and using the modified biochar with improved ionic conductivity as an artificial SEI on the surface of magnesium metal, it is expected to improve the electrochemical performance of the composite metal negative electrode. In addition, the rational conversion of biomass materials and waste into functional materials is an environmentally friendly and sustainable option for treating biomaterials and waste generated in daily life, manufacturing and agriculture. Biomass-based materials have been used in many practical applications.

[0004] Therefore, there is an urgent need for a simple and low-cost method to further improve the ionic conductivity of biochar so as to meet the demand that the modified biochar can be used as an artificial magnesium ion protective interface layer. Summary of the invention

[0005] In order to further improve the ionic conductivity of biochar as an artificial protective interface on the surface of magnesium metal, the present invention provides a method for preparing a biochar / magnesium composite negative electrode sheet with high ionic conductivity.

[0006] The method for preparing the biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity of the present invention is carried out according to the following steps:

[0007] 1. Raw material preparation: weigh biomass charcoal, metal matrix and hydrogen peroxide as raw materials;

[0008] 2. Precursor preparation:

[0009] The hydrogen peroxide in step 1 is prepared into a hydrogen peroxide aqueous solution, and then the biomass charcoal is placed in the hydrogen peroxide aqueous solution and stirred, and then filtered to obtain a mixture of hydrogen peroxide and biomass charcoal;

[0010] 3. Prefabricated body processing:

[0011] Residual hydrogen peroxide is removed from the mixture of hydrogen peroxide and biochar in step 2, and then the treated biochar is placed in a vacuum oven for drying to obtain a preform;

[0012] 4. Preparation of modified biomass carbon / magnesium composite materials:

[0013] The preform obtained in step three and the metal matrix in step one are prepared into a biomass carbon / magnesium composite negative electrode plate by a pressure infiltration process under a protective atmosphere.

[0014] The present invention has the following beneficial effects:

[0015] 1. The present invention provides a method for improving the ionic conductivity of biochar / magnesium composite materials, using hydrogen peroxide to chemically activate the biochar, so that the biochar produces a large number of defects and the specific surface area is significantly increased, the contact sites of magnesium ions are increased and the transmission path of magnesium ions is shortened, thereby further improving the chemical reaction rate and optimizing the ionic conductivity. The modified biochar / magnesium composite material is prepared by self-exhaust pressure infiltration technology. The modified biochar as an artificial SEI on the surface of the magnesium metal negative electrode significantly reduces the overpotential of the magnesium metal negative electrode sheet during the circulation process in a conventional electrolyte, and the reaction kinetics are effectively improved.

[0016] 2. The present invention realizes the rational conversion of biomass materials and waste into functional materials, which is an environmentally friendly and sustainable option for processing biomass materials and waste generated in daily life, manufacturing and agriculture. The present invention utilizes the high specific surface area and modulatable chemical components of porous carbon materials, which is beneficial to applications related to energy storage and conversion, and exerts its functional material properties.

[0017] 3. The raw material cost of the present invention is low, green, environmentally friendly and renewable. The electrochemical electrode is prepared in one piece, which is simple and effective. The artificial protective interface can effectively improve the performance through a simple activation treatment, which meets the requirements of industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM image of the modified biomass carbon / magnesium composite material obtained in Example 1;

[0019] Figure 2 The electrochemical impedance spectroscopy test results of the modified biomass carbon / magnesium composite material obtained in Example 1.

[0020] Figure 3 The electrochemical impedance spectroscopy test results of the unmodified biomass carbon / magnesium composite material obtained in Comparative Example 1. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.

[0022] Specific implementation method 1: The preparation method of the biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity in this implementation method is carried out according to the following steps:

[0023] 1. Raw material preparation: weigh biomass charcoal, metal matrix and hydrogen peroxide as raw materials;

[0024] 2. Precursor preparation:

[0025] The hydrogen peroxide in step 1 is prepared into a hydrogen peroxide aqueous solution, and then the biomass charcoal is placed in the hydrogen peroxide aqueous solution and stirred, and then filtered to obtain a mixture of hydrogen peroxide and biomass charcoal;

[0026] 3. Prefabricated body processing:

[0027] Residual hydrogen peroxide is removed from the mixture of hydrogen peroxide and biochar in step 2, and then the treated biochar is placed in a vacuum oven for drying to obtain a preform;

[0028] 4. Preparation of modified biomass carbon / magnesium composite materials:

[0029] The preform obtained in step three and the metal matrix in step one are prepared into a biomass carbon / magnesium composite negative electrode plate by a pressure infiltration process under a protective atmosphere.

[0030] This embodiment has the following beneficial effects:

[0031] 1. This embodiment provides a method for improving the ionic conductivity of biochar / magnesium composite materials, using hydrogen peroxide to chemically activate the biochar, so that the biochar produces a large number of defects and the specific surface area is significantly increased, the contact sites of magnesium ions are increased and the transmission path of magnesium ions is shortened, thereby further improving the chemical reaction rate and optimizing ion conductivity. The modified biochar / magnesium composite material is prepared using self-exhaust pressure infiltration technology. The modified biochar as an artificial SEI on the surface of the magnesium metal negative electrode significantly reduces the overpotential of the magnesium metal negative electrode sheet during the circulation process in a conventional electrolyte, and the reaction kinetics are effectively improved.

[0032] 2. This embodiment realizes the rational conversion of biomass materials and waste into functional materials, which is an environmentally friendly and sustainable choice for processing biomass materials and waste generated in daily life, manufacturing and agriculture. This embodiment utilizes the high specific surface area and modulatable chemical composition of porous carbon materials, which is beneficial to applications related to energy storage and conversion, and exerts its functional material properties.

[0033] 3. The raw material cost of this embodiment is low, green, environmentally friendly and renewable. The electrochemical electrode is prepared in one piece, which is simple and effective. The artificial protective interface can effectively improve the performance through a simple activation treatment, which meets the requirements of industrial production and application. Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the biochar described in step 1 is a block or powder. The biochar block has a three-dimensional interconnected pore structure.

[0034] Specific implementation method three: This implementation method is different from specific implementation method two in that: the particle size of the powder described in step one is 50 to 300 μm.

[0035] Specific embodiment four: This embodiment differs from any one of specific embodiments one to three in that: the metal matrix described in step one is pure magnesium and magnesium alloy, and the magnesium alloy is one or a combination of several of Mg-Al alloy, Mg-Al-Zn-Mn alloy, Mg-Al-Si alloy and Mg-Si alloy.

[0036] Specific implementation method 5: This implementation method is different from any one of specific implementation methods 1 to 4 in that the mass fraction of the hydrogen peroxide aqueous solution described in step 2 is 20-50%.

[0037] Specific embodiment 6: This embodiment is different from any one of specific embodiments 1 to 5 in that: the temperature at which the biochar described in step 2 is stirred in the hydrogen peroxide aqueous solution is 25 to 200°C.

[0038] Specific implementation method 7: This implementation method is different from any one of specific implementation methods 1 to 6 in that: the biochar described in step 2 is placed in the hydrogen peroxide aqueous solution and stirred for 2 to 48 hours.

[0039] Specific embodiment eight: This embodiment differs from any one of specific embodiments one to seven in that: the method for removing residual hydrogen peroxide from the mixture of hydrogen peroxide and biochar in step three is centrifugation or filtration, and then repeated washing with deionized water, wherein the centrifugal speed is 3000-5000rpm, and the centrifugal time is 0.5-1h.

[0040] Specific embodiment 9: This embodiment differs from any one of specific embodiments 1 to 8 in that: in the pressure infiltration process described in step 4, the preheating temperature is 600-650°C, the infiltration temperature is 800-890°C, and the protective atmosphere is helium, nitrogen or argon.

[0041] Specific embodiment ten: This embodiment differs from any one of specific embodiments one to nine in that the volume fraction of biomass carbon in the biomass carbon / magnesium composite negative electrode sheet described in step four is 60% to 80%, and the metal matrix is ​​the remainder.

[0042] The following examples are used to verify the beneficial effects of the present invention:

[0043] Embodiment 1:

[0044] The method for preparing the biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity is carried out according to the following steps:

[0045] 1. Raw material preparation: weigh biomass charcoal, metal matrix and hydrogen peroxide as raw materials;

[0046] The biomass charcoal is a block;

[0047] The metal matrix is ​​pure magnesium;

[0048] 2. Precursor preparation:

[0049] The hydrogen peroxide in step 1 is prepared into a hydrogen peroxide aqueous solution, and then the biomass charcoal is placed in the hydrogen peroxide aqueous solution and stirred, and then filtered to obtain a mixture of hydrogen peroxide and biomass charcoal;

[0050] The mass fraction of the aqueous hydrogen peroxide solution is 30%;

[0051] The biochar is placed in the hydrogen peroxide aqueous solution and stirred at a temperature of 100°C;

[0052] The biochar is placed in the hydrogen peroxide aqueous solution and stirred for 4 hours;

[0053] 3. Prefabricated body processing:

[0054] Residual hydrogen peroxide is removed from the mixture of hydrogen peroxide and biochar in step 2, and then the treated biochar is placed in a vacuum oven for drying to obtain a preform;

[0055] The hydrogen peroxide removal process is as follows: after filtering the hydrogen peroxide solution, the block of biomass char is repeatedly washed with deionized water.

[0056] 4. Preparation of modified biomass carbon / magnesium composite materials:

[0057] The preform obtained in step three and the metal matrix in step one are prepared into a biomass carbon / magnesium composite negative electrode plate by a pressure infiltration process under a protective atmosphere.

[0058] The protective atmosphere is nitrogen;

[0059] In the pressure infiltration process, the preheating temperature is 640°C and the infiltration temperature is 880°C;

[0060] The volume fraction of biomass carbon in the biomass carbon / magnesium composite negative electrode sheet is 70%, and the metal matrix is ​​the balance.

[0061] Comparative Example 1:

[0062] The preparation method of the unmodified biomass carbon / magnesium composite material is carried out according to the following steps:

[0063] 1. Weigh lump biochar and pure magnesium as raw materials;

[0064] 2. Preparation of biomass carbon / magnesium composite materials:

[0065] Unmodified biochar / magnesium composites were prepared by pressure infiltration under nitrogen atmosphere, wherein pure magnesium was prepared into magnesium melt, and then the block biochar was preheated, and then pressure infiltrated into the magnesium melt to fill all the three-dimensional interconnected pores in the block biochar; the preheating temperature was 640°C, and the pressure infiltration temperature was 880°C. The volume fraction of biochar in the composite material was 70%, and the metal matrix was the remainder.

[0066] Figure 1 This is the SEM image of the modified biomass carbon / magnesium composite material obtained in Example 1; as can be seen from Figure 1, the interface bonding between the modified biomass carbon and the metallic magnesium in the modified biomass carbon / magnesium composite material is good, and there is almost no interface debonding phenomenon.

[0067] Figure 2 The electrochemical impedance spectroscopy test results of the modified biomass carbon / magnesium composite material obtained in Example 1. Figure 3 The electrochemical impedance spectroscopy test results of the unmodified biomass carbon / magnesium composite material obtained in Comparative Example 1. After testing, the ionic resistance of the two systems was obtained by electrochemical impedance spectroscopy (EIS), and the typical Nyquist curve is as follows Figure 2 and Figure 3 As shown in Figure 2, the ionic conductivity of the unmodified biomass carbon / magnesium composite system is 4×10 -5 S cm -1 The ionic conductivity of the modified biomass carbon / magnesium composite system is 8×10 -4 S cm -1Compared with the unmodified biomass carbon / magnesium, the ionic conductivity is significantly increased, which makes the modified biomass carbon / magnesium composite electrode have a smaller overpotential during the cycle process.

[0068] Embodiment 2:

[0069] The method for preparing the biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity is carried out according to the following steps:

[0070] 1. Raw material preparation: weigh biomass charcoal, metal matrix and hydrogen peroxide as raw materials;

[0071] The biomass charcoal is in the form of powder; the particle size of the powder is 100 μm;

[0072] The metal matrix is ​​pure magnesium;

[0073] 2. Precursor preparation:

[0074] The hydrogen peroxide in step 1 is prepared into a hydrogen peroxide aqueous solution, and then the biomass charcoal is placed in the hydrogen peroxide aqueous solution and stirred, and then filtered to obtain a mixture of hydrogen peroxide and biomass charcoal;

[0075] The mass fraction of the aqueous hydrogen peroxide solution is 50%;

[0076] The temperature of the biochar being stirred in the hydrogen peroxide aqueous solution is 80°C;

[0077] The biochar is placed in the hydrogen peroxide aqueous solution and stirred for 6 hours;

[0078] 3. Prefabricated body processing:

[0079] Residual hydrogen peroxide is removed from the mixture of hydrogen peroxide and biochar in step 2, and then the treated biochar is placed in a vacuum oven for drying to obtain a preform;

[0080] The hydrogen peroxide removal process is: repeated washing with deionized water after centrifugation, wherein the centrifugal speed is 4000 rpm and the centrifugal time is 0.5 h.

[0081] 4. Preparation of modified biomass carbon / magnesium composite materials:

[0082] The preform obtained in step three and the metal matrix in step one are prepared into a biomass carbon / magnesium composite negative electrode plate by a pressure infiltration process under a protective atmosphere.

[0083] The protective atmosphere is nitrogen;

[0084] In the pressure infiltration process, the preheating temperature is 620°C and the infiltration temperature is 870°C;

[0085] The volume fraction of biomass carbon in the biomass carbon / magnesium composite negative electrode plate is 65%, and the metal matrix is ​​the balance.

[0086] Comparative Example 2:

[0087] The preparation method of the unmodified biomass carbon / magnesium composite material is carried out according to the following steps:

[0088] 1. Weigh 100 μm biomass carbon powder and pure magnesium as raw materials;

[0089] 2. Preparation of biomass carbon / magnesium composite materials:

[0090] An unmodified biochar / magnesium composite material was prepared by pressure infiltration under a nitrogen atmosphere, wherein pure magnesium was prepared into a magnesium melt, and then the biochar preform was preheated at a preheating temperature of 620° C. and a pressure infiltration temperature of 870° C. The volume fraction of the biochar in the composite material was 65%, and the metal matrix was the remainder.

[0091] After testing, the modified biomass carbon / magnesium of Example 2 and the unmodified biomass carbon / magnesium of Comparative Example 2 were subjected to EIS testing. The results showed that the ionic conductivity of the unmodified biomass carbon / magnesium composite material system was 4×10 -6 S cm -1 The ionic conductivity of the modified biomass carbon / magnesium composite system is 7×10 -5 S cm -1 The ionic conductivity of the modified biomass carbon / magnesium composite electrode was significantly increased.

[0092] Embodiment 3:

[0093] The method for preparing the biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity is carried out according to the following steps:

[0094] 1. Raw material preparation: weigh biomass charcoal, metal matrix and hydrogen peroxide as raw materials;

[0095] The biomass charcoal is a block;

[0096] The metal matrix is ​​AZ91 alloy (Mg-9Al-0.7Zn-0.2Mn, wt.%)

[0097] 2. Precursor preparation:

[0098] The hydrogen peroxide in step 1 is prepared into a hydrogen peroxide aqueous solution, and then the biomass charcoal is placed in the hydrogen peroxide aqueous solution and stirred, and then filtered to obtain a mixture of hydrogen peroxide and biomass charcoal;

[0099] The mass fraction of the aqueous hydrogen peroxide solution is 20%;

[0100] The temperature of the biochar being stirred in the hydrogen peroxide aqueous solution is 120°C;

[0101] The biochar is placed in the hydrogen peroxide aqueous solution and stirred for 2 hours;

[0102] 3. Prefabricated body processing:

[0103] Residual hydrogen peroxide is removed from the mixture of hydrogen peroxide and biochar in step 2, and then the treated biochar is placed in a vacuum oven for drying to obtain a preform;

[0104] The hydrogen peroxide removal process is: repeated washing with deionized water after centrifugation, wherein the centrifugal speed is 3000 rpm and the centrifugal time is 1 hour.

[0105] 4. Preparation of modified biomass carbon / magnesium composite materials:

[0106] The preform obtained in step three and the metal matrix in step one are prepared into a biomass carbon / magnesium composite negative electrode plate by a pressure infiltration process under a protective atmosphere.

[0107] The protective atmosphere is nitrogen;

[0108] In the pressure infiltration process, the preheating temperature is 600°C and the infiltration temperature is 850°C;

[0109] The volume fraction of biomass carbon in the biomass carbon / magnesium composite negative electrode sheet is 60%, and the metal matrix is ​​the balance.

[0110] Comparative Example 3:

[0111] The preparation method of the unmodified biomass carbon / magnesium composite material is carried out according to the following steps:

[0112] 1. Weigh lump biochar and AZ91 alloy (Mg-9Al-0.7Zn-0.2Mn, wt.%) as raw materials;

[0113] 2. Preparation of biomass carbon / magnesium composite materials:

[0114] Unmodified biochar / magnesium composite materials were prepared by pressure infiltration under a protective atmosphere, wherein pure magnesium was prepared into a magnesium melt, and then the block biochar was preheated, and then pressure infiltrated into the magnesium melt to fill all three-dimensional interconnected pores in the block biochar; the preheating temperature was 600°C, and the pressure infiltration temperature was 850°C. The volume fraction of the biochar in the composite material was 60%, and the metal matrix was the remainder.

[0115] After testing, the modified biomass carbon / magnesium of Example 3 and the unmodified biomass carbon / magnesium of Comparative Example 3 were subjected to EIS testing. The results showed that the ionic conductivity of the unmodified biomass carbon / magnesium composite material system was 1×10 -6 S cm -1 The ionic conductivity of the modified biomass carbon / magnesium composite system is 8×10 -6 S cm -1 , the ionic conductivity of the modified biomass carbon / magnesium composite electrode is effectively increased.

Claims

1. A method for preparing a biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity, characterized in that: The method for preparing the biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity is carried out according to the following steps:

1. Raw material preparation: weigh biomass charcoal, metal matrix and hydrogen peroxide as raw materials; 2. Precursor preparation: The hydrogen peroxide in step 1 is prepared into a hydrogen peroxide aqueous solution, and then the biomass charcoal is placed in the hydrogen peroxide aqueous solution and stirred, and then filtered to obtain a mixture of hydrogen peroxide and biomass charcoal; 3. Prefabricated body processing: Residual hydrogen peroxide is removed from the mixture of hydrogen peroxide and biochar in step 2, and then the treated biochar is placed in a vacuum oven for drying to obtain a preform; 4. Preparation of modified biomass carbon / magnesium composite materials: The preform obtained in step three and the metal matrix in step one are prepared into a biomass carbon / magnesium composite negative electrode plate by a pressure infiltration process under a protective atmosphere.

2. The method for preparing a biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity according to claim 1, characterized in that: The biochar described in step 1 is in the form of blocks or powder.

3. The method for preparing a biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity according to claim 2, characterized in that: The particle size of the powder in step 1 is 50 to 300 μm.

4. The method for preparing a biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity according to claim 1, characterized in that: The metal matrix described in step 1 is pure magnesium and magnesium alloy, and the magnesium alloy is one of Mg-Al alloy, Mg-Al-Zn-Mn alloy, Mg-Al-Si alloy and Mg-Si alloy or a combination of several thereof.

5. The method for preparing a biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity according to claim 1, characterized in that: The mass fraction of the hydrogen peroxide aqueous solution in step 2 is 20-50%.

6. The method for preparing a biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity according to claim 1, characterized in that: The biochar in step 2 is placed in the hydrogen peroxide aqueous solution and stirred at a temperature of 25 to 200°C.

7. The method for preparing a biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity according to claim 1, characterized in that: The biochar described in step 2 is placed in the aqueous hydrogen peroxide solution and stirred for 2 to 48 hours.

8. The method for preparing a biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity according to claim 1, characterized in that: The method of removing residual hydrogen peroxide from the mixture of hydrogen peroxide and biochar in step 3 is centrifugation or filtration, and then repeated washing with deionized water, wherein the centrifugal speed is 3000-5000 rpm and the centrifugal time is 0.5-1h.

9. The method for preparing a biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity according to claim 1, characterized in that: In the pressure infiltration process described in step 4, the preheating temperature is 600-650° C., the infiltration temperature is 800-890° C., and the protective atmosphere is helium, nitrogen or argon.

10. The method for preparing a biomass carbon / magnesium composite negative electrode sheet with high ionic conductivity according to claim 1, characterized in that: The volume fraction of biomass carbon in the biomass carbon / magnesium composite negative electrode sheet described in step 4 is 60% to 80%, and the metal matrix is ​​the balance.

Citation Information

Patent Citations

  • Passivation modification processing method for ordered mesoporous carbon surface, hydrophilic ordered mesoporous carbon and application of ordered mesoporous carbon

    CN110407188A

  • Method for modifying nano activated carbon pore structure through microwave-assisted hydrogen peroxide fed-batch

    CN110482551A

  • Preparation method and application of biomass activated carbon material

    CN110615435A

  • Biomass-based activated carbon material with high specific surface area and application thereof

    CN118039367A

  • Carbon material and method for producing same

    US20120034463A1